2018
DOI: 10.1093/femsec/fiy092
|View full text |Cite
|
Sign up to set email alerts
|

Native bacteria promote plant growth under drought stress condition without impacting the rhizomicrobiome

Abstract: Inoculation of plants with beneficial plant growth-promoting bacteria (PGPB) emerges a valuable strategy for ecosystem recovery. However, drought conditions might compromise plant-microbe interactions especially in semiarid regions. This study highlights the effect of native PGPB after 1 year inoculation on autochthonous shrubs growth and rhizosphere microbial community composition and activity under drought stress conditions. We inoculated three plant species of semiarid Mediterranean zones, Thymus vulgaris, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 82 publications
(90 reference statements)
0
40
0
3
Order By: Relevance
“…The role of microbial rhizosphere communities in plant growth and health is widely investigated, with most studies focusing on the effects of beneficial bacteria [18,31,49,50]. However, understanding of how agricultural land practices manipulate rhizosphere community's assembly and thus influence plant productivity is needed [51].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of microbial rhizosphere communities in plant growth and health is widely investigated, with most studies focusing on the effects of beneficial bacteria [18,31,49,50]. However, understanding of how agricultural land practices manipulate rhizosphere community's assembly and thus influence plant productivity is needed [51].…”
Section: Discussionmentioning
confidence: 99%
“…The performance of the rhizosphere community, e.g., nutrient acquisition, growth hormone productions, and defense against diseases, is a major determinant of the plant phenotype [25,26]. Detailed investigations of the interactions between plants and microorganisms have revealed that plants can respond to rhizosphere microbes in different ways [27][28][29][30][31]. According to a recent study, root exudatemediated changes in the rhizosphere community of peanut (Arachis hypogaea) seedlings strongly influence the physiology and further development of peanut plants [32].…”
Section: Introductionmentioning
confidence: 99%
“…Among the different tools available to increase productivity in agriculture, the use of plant growth-promoting bacteria (PGPB) has demonstrated great potential to achieve the goal of sustainability. PGPB can directly contribute to plant nutrition and can alleviate the detrimental effects caused by biotic and abiotic stresses to which field crops are subjected; PGPB can also indirectly improve soil fertility and quality by at least partially substituting for the use of chemical inputs [1][2][3][4]. Nevertheless, despite the large number of studies reporting the advantages of the use of PGPB as inoculants within commercial agricultural crops, their use as a regular agricultural practice on nonleguminous crop species is still underexplored in comparison with the amount of agricultural lands annually cultivated worldwide [5].…”
Section: Introductionmentioning
confidence: 99%
“…The PGPR strain can protect from the attacks of Ralstonia solanacearum on tomatoes and Colletotrichum gloeosporioides on cayenne pepper and cucumber. Research [16], on the inoculation of plants with beneficial plant growth promoting bacteria (PGPB), raises a valuable strategy for restoring ecosystems. This study highlights the effects of native PGPB after 1 year inoculation on native shrub growth and rhizosphere composition and activity of microbial communities under drought stress conditions.…”
Section: Pekinensis)mentioning
confidence: 99%